Familial adenomatous polyposis in dogs: hereditary gastrointestinal polyposis in Jack Russell Terriers with germline APC mutations. (23rd May 2020) - Yoshizaki, Kyoko; Hirata, Akihiro; Nishii, Naohito; Kawabe, Mifumi; Goto, Minami; Mori, Takashi; Sakai, Hiroki
Abstract: Many hereditary disorders in dogs have equivalents in humans and thus attract attention as natural animal models. Breed predisposition to certain diseases often provides promising clues to explore novel hereditary disorders in dogs. Recently, cases of gastrointestinal (GI) polyps in Jack Russell Terriers (JRTs) have increased in Japan. In 21 affected JRTs, polyps were found in either or both the stomach and colorectum, with a predilection for the gastric antrum and rectum. Multiple polyps were found in 13 of 21 examined dogs, including 5 dogs with both gastric and colorectal polyps. Some dogs were found to have GI polyps at an early age, with the youngest case being 2.3 years old. Histopathologically, 43 of 46 GI polyps (93.5%) were diagnosed as adenomas or adenocarcinomas. Immunohistochemical analysis revealed cytoplasmic and nuclear accumulation of β-catenin in the tumor cells. As in the case of human patients with familial adenomatous polyposis, all examined JRTs with GI polyps ( n = 21) harbored the identical heterozygous germline APC mutations, represented by a 2-bp substitution (c.[462A>T; 463A>T]). The latter substitution was a non-sense mutation (p.K155X) resulting in a truncated APC protein, thus suggesting a strong association with this cancer-prone disorder. Somatic mutation and loss of the wild-type APC allele were detected in the GI tumors of JRTs, suggesting that biallelic APC inactivation was involved in tumor development. This study demonstrated that despite differences in the disease conditions between human and dog diseases, germline APC mutation confers a predisposition to GI neoplastic polyps in both dogs and humans. Abstract : We identified a novel hereditary gastrointestinal polyposis caused by identical germline APC mutations in dogs. Our data demonstrate that a germline APC mutation confers a predisposition to gastrointestinal neoplastic polyps in dogs, as in the case with humans.